Biological literacy skills of senior high school student using local potential-based biodiversity question sets - Arkhis Emilia Hidayat; W. Wisanti; I. Isnawati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
One of the efforts to improve the quality of education in Indonesia is through learning by integrating environmental culture. Environmental culture can be packaged in more meaningful learning through biological literacy. This study aims to assess the biological literacy skills of high school students using local potential-based biodiversity question sets. This study includes research with quantitative descriptive methods that aim to describe the biological literacy skills of high school tenth grade students. Biological literacy research data consists of 4 indicators, namely nominal, conceptual, multidimensional and functional. The number of participants was 60 high school students. The initial stage used expert judgment for content validation which was tested by 3 expert validators. Construct validation was carried out based on data collection with the results of 12 question sets that were declared valid. Data analysis of the percentage of students who answered correctly on biological literacy indicators were all at a high level, namely on nominal indicators of 69.37%, conceptual indicators of 70%, functional indicators of 66.87%, and multidimensional indicators of 70%. It is concluded that the local wisdom-based biodiversity question set can be used to measure students' biological literacy skills in schools.